A preclinical evaluation of the response of repairing the DNA of MCF7 breast cancer cells after exposure to probiotic bacteria - Afak Zaidi; Luma Al-Abdulwahid; Susan Hasan (Microbes and Infectious Diseases, 2025)
Background: Breast cancer is the most common cancer among women worldwide. Through the regulation of numerous cellular processes involved in DNA damage and repair have an impact on DNA damage response signaling. Probiotics may assist in repairing DNA damage by promoting tissue regeneration and activating DNA repair enzymes. Methods: The inhibition of MCF7 cells by Lactobacillus planetarium Treatment 1(T1) and a combination of 8 strains of probiotics Treatment 2(T2) was done. T1 and T2 were assessed by crystal violet assay and genetic changes were conducted by comet assay. The repair of DNA damage was compared with control by using CASP software analysis image. Results: Both treatments, T1 and T2, showed no significant cytotoxic effect on breast cancer cell lines. Curve of images analysis demonstrated that the potential role for T1 and T2 in breast cancer treatment as showing green small tail and red large head compare with control. MCF7 cells exposed to T1 for 48 h and 72 h showed a significant increase in L Tail (P≤0.005), Head DNA (P≤0.001) and Tail DNA (P≤0.001) compare with control. In contrast to the control, MCF7 cells treated to T2 for 48 h and 72 h demonstrated a substantial increase in L Head (P≤0. 5), L Tail (P≤0.5), L comet (P≤0.5), Head DNA (P≤0.5), and Tail DNA (P≤0.5). Conclusion, probiotics bacteria could support repairing DNA damage, making them a natural agent for the treatment of breast cancer. However, these results need more investigation to identify the signaling pathway that used in the repair.